CHARACTERIZATION OF OIL PALM SAP (ELAEIS GUINEENSIS JACQ. RESULTS OF ZERO WASTE BASED WASTE TREATMENT) - Fadlilah Widyaningsih; Reno Irwanto; Delita Br Panjaitan (JURNAL KESMAS DAN GIZI (JKG), 2023)
Oil palm (Elaeis guineensis Jacq.) is a productive plant where every part can be utilized. Not only the flesh and kernels of the palm fruit can be extracted into oil, but the by-products produced during the production process and their waste can also be processed into something useful. One of the zero waste-based palm oil waste processing that is being developed at this time is the use of non-productive oil palm tree trunks during the replanting period, namely by taking the sap. This research is a quasi-experimental study with a factorial experiment design which aims to analyze the quality of palm sap resulting from zero waste-based waste treatment at several variations of tapping time and duration. In this study, there were 2 factors in cross classification, namely factor A (time) and factor B (tapping time). Factor A consists of 2 levels, namely A1: Morning, A2: Afternoon and factor B consists of 3 levels, namely B1: 4 hours, B2: 8 hours, B3: 12 hours. Treatment is a combination of both. To find out the differences in each treatment group, a bivariate test was performed with one way annova test with a 95% confidence level and continued with Duncan's test. The results showed that the combination of tapping time and length of time was significantly different for pH, moisture content, total acid, total solids and alcohol content of palm sap but not significantly different for ash content of palm sap.